PENINGKATAN PEMAHAMAN GURU SHADOW DAN ORANG TUA TENTANG POLA MAKAN SEHAT BAGI ANAK AUTISM SPECTRUM DISORDER DI LEMBAGA INKLUSIF AL-USWAH PAMEKASAN - Makki, M.Ismail; Aflahah (CV. Jendela Gagasan, 2025)
Children with Autism Spectrum Disorder (ASD) often experience sensory issues, food selectivity, and behavioral difficulties that are strongly influenced by dietary patterns. This community engagement program aimed to improve the knowledge and practical skills of shadow teachers and parents in managing appropriate nutritional intake for ASD students at Al-Uswah Inclusive School, Pamekasan. The program was conducted from September to November 2025 using a Participatory Learning and Action (PLA) approach through training, workshops, individual mentoring, and monitoring. A total of 35 shadow teachers and 35 parents participated. Pre-test and post-test evaluations indicated a 35 percent average increase in understanding related to nutrition, foods to avoid, and menu planning skills. Observation following two weeks of dietary implementation showed behavioral improvements among ASD students, including increased concentration (60 percent), reduced tantrums (50 percent), and more regular sleep patterns (70 percent). The program also strengthened school–parent collaboration through the creation of a communication forum and a practical nutrition booklet. These findings demonstrate that participatory nutrition education effectively enhances knowledge and dietary practices for ASD children and can serve as a replicable non-pharmacological intervention model for other inclusive institutions.